The Role of Acromioplasty in the Treatment of Shoulder Impingement Syndrome Acromioplasty in the Treatment of Shoulder Impingement - Rüştü Nuran; Cemal Kural; Ali Akın Uğraş (Haseki Tıp Bülteni, 2011)
Aim: The results of open acromioplasty procedures were investigated for shoulder impingement syndrome in patients who did not respond to conservative treatment. Methods: Twenty cases of shoulder impingement syndrome who did not respond to conservative treatment were investigated prospectively. The shoulder abduction and flexion range of motion and muscle power were measured preoperatively and postoperatively. Anteroposterior, neutral, axillary and impingement radiographs were taken. Shoulder magnetic resonance imaging (MRI) was performed. Clinical assessment was performed by the Constant shoulder score. Results: Results of MRI revealed that 20 cases had type 1, 2 and 3 acromion in 3, 9 and 8 patients, respectively. The mean followup time was 16 months. Compared to preoperative conditions, the results in 80% of cases were rated as perfect (p<0.000), since all cases had gained both significantly more range of motion (p<0.000) and muscle power (p<0.000), in addition to decreased pain in all cases (p<0.000). Four cases who had been rated as good had common features as advance age, traumatic etiology and inadequate rehabilitation. Conclusion: Open acromioplasty surgery reduces pain, increases range of motion and is an effective treatment option in cases of shoulder impingement syndrome not responding to conservative treatment. (The Me di cal Bul le tin of Ha se ki 2011; 49: 141-4)